VD_FINDINFO HC / 2020 / 574 vom 4. September 2020 - VD Tribunal cantonal (2020)
CONTRAT D'ENTREPRISE, DEVIS, DÉCOMPTESENS GÉNÉRAL, PRIX FERME, PRIX EFFECTIF, CONSTATATION DES FAITS | 1 CO, 18 al. 1 CO, 373 CO, 374 CO